Structural basis of ribosomal RNA transcription regulation - Yeonoh Shin (Nature Portfolio, 2021)
Ribosomal RNA (rRNA) expression is regulated at the initiation stage of RNA synthesis. Here, the authors report cryo-EM structures of E. coli RNA polymerase and rRNA promoter complex with DksA/ppGpp on the way to open complex formation, identifying key steps in promoter recognition and opening.